Constructing a continuous hemodiafiltration‐type circulatory model of acute kidney injury in pigs. Issue 3 (15th March 2022) - Horikawa, Takumi; Maehata, Junichi; Hashimoto, Fumihiro; Ikuhara, Toshihiko; Araki, Hitomi; Umeno, Hiroshi; Sano, Yusuke; Ishikawa, Chika; Takagi, Hisayoshi; Watanabe, Atsushi; Koizumi, Toshinori
Abstract: Introduction: Animal‐model experimental systems capable of reflecting the effects of devices for continuous renal replacement therapy (CRRT) on living organisms are limited; thus, aimed to construct an animal model of AKI‐CRRT using pigs. Methods: Pigs were subjected to renal artery ischemia–reperfusion injury (IRI) and then to a maximum of 24 h of continuous hemodiafiltration (CHDF)‐type CRRT. Results: Post‐IRI, pigs' creatinine levels rose threefold, and they exhibited 24 h of anuria and clear aggravation of oxidative stress, demonstrating successful induction of AKI for CRRT. Post‐CRRT, no significant changes in their vital signs or hematological parameters were observed. Creatinine and blood urea nitrogen clearance, as well as suppression of increases in oxidative stress, were also confirmed. Conclusion: We believe that the use of our model can enable the preclinical evaluation of the effects of under‐development CRRT devices on living organisms under conditions similar to those encountered in an actual clinical setting.